2021
DOI: 10.3389/fmicb.2021.643679
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Shift in the Microbiome of Composts That Are Optimized for a Better Fit-for-Purpose in Growing Media

Abstract: Three characteristics are considered key for optimal use of composts in growing media: maturity, pH and organic matter content. Maturation is a critical step in the processing of composts contributing to compost quality. Blending of composts with chopped heath biomass, sieving out the larger fraction of composts and acidification of composts by adding elemental sulfur may be used either to increase organic matter content or to reduce pH for a better fit in growing media. While several studies have shown the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…The composting process furthers decomposition, and through mixing, sieving and in many cases, acidification, compost matures and thus, its microbial composition changes. As Pot et al (2021) [162] observed, among the variables, raw materials had the highest influence on the microbiome of the end product. While the maturation of compost definitely increased microbial diversity, blending and acidification are tools that modify and optimise the compost microbiome.…”
Section: Compost Microbiomementioning
confidence: 85%
“…The composting process furthers decomposition, and through mixing, sieving and in many cases, acidification, compost matures and thus, its microbial composition changes. As Pot et al (2021) [162] observed, among the variables, raw materials had the highest influence on the microbiome of the end product. While the maturation of compost definitely increased microbial diversity, blending and acidification are tools that modify and optimise the compost microbiome.…”
Section: Compost Microbiomementioning
confidence: 85%
“…At last, the effect of enrichment of product B was tested using the edgeR package (version 3.28.0) [ 93 ] as described in detail in De Tender et al [ 94 ]. According to Pot et al [ 95 ], normalization based on the trimmed mean of M-values (TMM) was applied to correct for differences in library size of the count table. A design matrix was defined based on the experimental design.…”
Section: Methodsmentioning
confidence: 99%
“…Composted materials such as composted bark and green waste compost have a much more diverse microbial community than other plant-growing media materials [50,65]. The compost feedstock is an important determinant of the compost microbiome, and compost maturation increases microbial diversity, favoring beneficial microbes [65].…”
Section: The Role Of Plant-growing Media In Microbiome Functioningmentioning
confidence: 99%
“…Composted materials such as composted bark and green waste compost have a much more diverse microbial community than other plant-growing media materials [50,65]. The compost feedstock is an important determinant of the compost microbiome, and compost maturation increases microbial diversity, favoring beneficial microbes [65]. In addition, composts have disease-suppressive properties linked to the compost's high microbial activity and the presence of beneficial microbes such as Trichoderma, Pseudomonas, Pantoea, and Bacillus spp., which are known to contribute to the biocontrol effect [65].…”
Section: The Role Of Plant-growing Media In Microbiome Functioningmentioning
confidence: 99%
See 1 more Smart Citation